2011
DOI: 10.1126/science.1209909
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Tumor Suppression Depends on BRCT Phosphoprotein Binding, But Not Its E3 Ligase Activity

Abstract: Germline mutations of the breast cancer 1 (BRCA1) gene are a major cause of familial breast and ovarian cancer. The BRCA1 protein displays E3 ubiquitin ligase activity, and this enzymatic function is thought to be required for tumor suppression. To test this hypothesis, we generated mice that express an enzymatically defective Brca1. We found that this mutant Brca1 prevents tumor formation to the same degree as does wild-type Brca1 in three different genetically engineered mouse (GEM) models of cancer. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
284
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(304 citation statements)
references
References 29 publications
18
284
2
Order By: Relevance
“…A mouse BRCA1 BRCT domain mutant, S1598F (corresponding to the S1655 of human BRCA1), disrupts its phospho-peptide binding activity (33). Previously, Ludwig and coworkers generated knock-in mice expressing I26A or S1598F mutant BRCA1 (34). In addition, they also created mice expressing a truncated form of BRCA1 after amino acid 924 (11tr), which lacks both BRCT domains.…”
Section: Brca1 Shows Strong Overlapping Interactions With Factors Invmentioning
confidence: 99%
“…A mouse BRCA1 BRCT domain mutant, S1598F (corresponding to the S1655 of human BRCA1), disrupts its phospho-peptide binding activity (33). Previously, Ludwig and coworkers generated knock-in mice expressing I26A or S1598F mutant BRCA1 (34). In addition, they also created mice expressing a truncated form of BRCA1 after amino acid 924 (11tr), which lacks both BRCT domains.…”
Section: Brca1 Shows Strong Overlapping Interactions With Factors Invmentioning
confidence: 99%
“…Although BRCA1 is implicated in many cellular processes, its role in HR (Moynahan et al, 1999;Stark et al, 2004) is thought to be critical for tumor suppression and maintenance of genomic stability (Silver and Livingston, 2012). Tumor suppressor functions of BRCA1 are mediated by the BRCA1 carboxyl-terminal (BRCT) domain (Shakya et al, 2011), a motif that binds phosphorylated serine motifs in three different DNA repair proteins: BACH1 (BRIP1), ABRAXAS (CCDC98), and CtIP (Rbbp8; Li and Greenberg, 2012). Among these complexes, BRCA1 association with CtIP has been implicated in nucleolytic resection of DNA double strand breaks (DSBs; Sartori et al, 2007;Chen et al, 2008).…”
mentioning
confidence: 99%
“…[18][19][20][21] A recent study identified the direct transcriptional play a role in other biological processes. 10 Furthermore, a more recent study has identified claspin, a coactivator of CHK1, as a substrate for BRCA1 Ub ligase and found that V26A (equivalent to murine and human I26A) mutant chicken DT40 cells have a defect in cellular response to DNA damage caused by topoisomerase inhibitors. 12 Clearly, more needs to be learned to fully appreciate the physiological significance of the BRCA1 E3 ligase targets.…”
Section: Functional Domains and Interacting Partners Of Brca1mentioning
confidence: 99%
“…7 The physiological significance of most of these interactions remains to be demonstrated. Interestingly, the E3 ligase activity of BRCA1 was shown to be dispensable for double strand break (DSB) repair as well as for tumor suppression in Brca1 mutant mice, 9,10 in which Brca1 carries a single amino acid substitution (I26A). This amino acid substitution was reported to have no effect on the interaction of BRCA1 with BARD1 but it disrupted the interaction with E2 conjugating enzymes.…”
Section: Functional Domains and Interacting Partners Of Brca1mentioning
confidence: 99%